NMR-based metabolomics profiling for radical scavenging and anti-aging properties of selected herbs - Hussin, Mahanom; Abdul Hamid, Azizah; Abas, Faridah; Ramli, Nurul Shazini; Jaafar, Ahmad Haniff; Roowi, Suri; Abdul Majid, Nordiana; Pak Dek, Mohd Sabri (MDPI, 2019)
Herbs that are usually recognized as medicinal plants are well known for their therapeutic effects and are traditionally used to treat numerous diseases, including aging. This study aimed to evaluate the metabolite variations among six selected herbs namely Curcurma longa, Oenanthe javanica, Vitex negundo, Pluchea indica, Cosmos caudatus and Persicaria minus using proton nuclear magnetic resonance (1H-NMR) coupled with multivariate data analysis (MVDA). The free radical scavenging activity of the extract was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azinobis(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) and oxygen radical absorbance capacity (ORAC) assay. The anti-aging property was characterized by anti-elastase and anti-collagenase inhibitory activities. The results revealed that P. minus showed the highest radical scavenging activities and anti-aging properties. The partial least squares (PLS) biplot indicated the presence of potent metabolites in P. minus such as quercetin, quercetin-3-O-rhamnoside (quercitrin), myricetin derivatives, catechin, isorhamnetin, astragalin and apigenin. It can be concluded that P. minus can be considered as a potential source for an anti-aging ingredient and also a good free radical eradicator. Therefore, P. minus could be used in future development in anti-aging researches and medicinal ingredient preparations.